A systematic literature review of the clinical and health economic burden of schizophrenia in privately insured patients in the United States - Zhang W; Amos TB; Gutkin SW; Lodowski N; Giegerich E; Joshi K (Dove Medical Press, 2018)
Wenjie Zhang,1 Tony B Amos,2 Stephen W Gutkin,1 Nicole Lodowski,1 Emma Giegerich,1 Kruti Joshi2 1WG US Advanced Health Analytics (WG AHA), Stamford, CT, USA; 2Janssen Scientific Affairs, LLC, Titusville, NJ, USA Purpose: The aim of this study was to conduct a systematic literature review on the burden of schizophrenia in privately insured US patients.Materials and methods: A systematic literature review of English language peer-reviewed journal articles of observational studies published from 2006 to 2016 was conducted using EMBASE/MEDLINE databases. Abstracts covering substantial numbers of patients with schizophrenia or schizoaffective disorder (i.e., N ≥ 100) were included for full-text review. Articles that did not clearly specify private insurance types were excluded.Results: A total of 25 studies were reviewed; 10 included only privately insured patients; and 15 included a mix of different types of insurance. The review of the clinical burden of schizophrenia revealed the following: compared to patients with no mental disorders, those with schizophrenia had significantly increased odds of systemic disorders and both alcohol and substance abuse. Antipsychotic (AP) adherence was low, ranging from 31.5% to 68.7%. The medication possession ratio for AP adherence ranged from 0.22 to 0.73. The review of the health economic burden of schizophrenia revealed the following: patients with a recent (vs. chronic) diagnosis of schizophrenia had significantly higher frequencies of emergency department visits and hospitalizations and greater length of stay (LOS) and total annual per-capita costs. Mean all-cause hospitalizations and LOS decreased significantly after (vs. before) initiating long-acting injectable APs (LAIs). Patients also had significantly decreased mean all-cause, and schizophrenia-related, hospitalization costs after initiating LAIs. Total direct per-capita costs of care (but not pharmacy costs) for patients who were nonadherent to their oral APs within the first 90 days of their index event were significantly higher (vs. early adherent patients). Despite these potential benefits, only 0.25%–13.1% of patients were treated with LAIs across all studies.Conclusion: Privately insured US patients with schizophrenia experience a substantial clinical and health economic burden related to comorbidities, acute care needs, nonadherence, and polypharmacy and have relatively low use of LAIs. Further study is warranted to understand prescribing patterns and clinical policies related to this patient population. Keywords: adherence, burden of illness, comorbidity, cost, health resource utilization, schizophrenia